A C-Terminal Fragment of Chlorotoxin Retains Bioactivity and Inhibits Cell Migration - Dastpeyman, Mohadeseh; Giacomin, Paul; Wilson, David; Nolan, Matthew J.; Bansal, Paramjit S.; Daly, Norelle L. (Frontiers in Pharmacology, 2019)
Chlorotoxin was originally isolated from the venom of the Israeli scorpion Leiurus quinquestriatus, and has potential as a tumour imaging agent based on its selective binding to tumour cells. Several targets have been suggested for chlorotoxin including voltage-gated chloride channels, and it has been shown to have anti-angiogenic activity and inhibit cell migration. The structure of chlorotoxin is stabilized by four disulfide bonds and contains -sheet and helical structure. Interestingly, the reduced form has previously been shown to inhibit cell migration to the same extent as the wild type, but structural analysis indicates that the reduced form of the peptide does not maintain the native secondary structure and appears unstructured in solution. This lack of structure suggests that a short stretch of amino acids might be responsible for the bioactivity. To explore this hypothesis we have synthesised fragments of chlorotoxin without disulfide bonds. As expected for such small peptides, NMR analysis indicated that the peptides were unstructured in solution. However, the peptide corresponding to the eight C-terminal residues, inhibited cell migration, in contrast to the other fragments. Our results suggest that the C-terminal region plays a critical role in the bioactivity of chlorotoxin.